Increasing Equity and Increasing School Performance ’’Conflicting or Compatible Goals?:Addressing the Issues in - Powers, Jeanne M. (Education Policy Analysis Archives, 2004)
This work addresses some of the arguments regarding equity in public education versus school performance at issue in the case of Williams v. State of California. The plaintiff’s expert witnesses have argued that the state is responsible to reduce the inequities in California’s public educational system. In contrast, the state’s witnesses argue that some of the plaintiff’s proposals have limited educational effects at the cost of reducing local autonomy. In this paper, I use four years of data from California’s Public Schools Accountability Act (PSAA) to evaluate these claims.